1999
DOI: 10.1046/j.1365-2133.1999.02660.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in skin barrier function in patients with atopic dermatitis after treatment with a moisturizing cream (Canoderm®)

Abstract: Patients with atopic skin show a defective barrier function both in rough and in clinically normal skin, with an increasing risk of developing contact dermatitis. Moisturizing creams are often used in the treatment of dry skin. The purpose of this study was to investigate the influence of treatment with a urea-containing moisturizer on the barrier properties of atopic skin. Fifteen patients with atopic dermatitis treated one of their forearms twice daily for 20 days with a moisturizing cream. Skin capacitance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
6
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(145 citation statements)
references
References 25 publications
6
127
6
6
Order By: Relevance
“…Frequent moisturization alleviates the discomfort associated with xerosis, helps to repair the skin barrier, and reduces the quantity and potency of pharmacologic interventions. 37,38 In a British study evaluating 51 children with AD, parents were educated on the proper use of moisturizers and topical treatments by a nurse specialist. During the study period, the quantity of moisturizer used increased 800% (average use of 426 g per week per patient) while the severity of AD decreased and the percentage of patients having to use moderate or potent topical steroids decreased.…”
Section: Treatment Principlesmentioning
confidence: 99%
“…Frequent moisturization alleviates the discomfort associated with xerosis, helps to repair the skin barrier, and reduces the quantity and potency of pharmacologic interventions. 37,38 In a British study evaluating 51 children with AD, parents were educated on the proper use of moisturizers and topical treatments by a nurse specialist. During the study period, the quantity of moisturizer used increased 800% (average use of 426 g per week per patient) while the severity of AD decreased and the percentage of patients having to use moderate or potent topical steroids decreased.…”
Section: Treatment Principlesmentioning
confidence: 99%
“…AD has been shown to be accompanied by impairement in the epidermal barrier function including reduced water content and an augmentation in TEWL due to the alteration of SC lipid profile. In mild and moderate AD, moisturizing and emollient creams are known to be effective through an increase of skin hydration and improvement of barrier function [19][20][21][22] . Tabata et al 21 indeed demonstrated that repeated daily applications of moisturizers, without any pharmacologically active agent, can induce long-lasting hydration effects in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bu da irritan ve alerjen maddelerin deri üzerinden penetrasyonunu önler. Yumuşa-tıcı ürünlerin dolaylı olarak antienflamatuar etkilerinin de bulunduğu da düşünülmektedir [8,29]. Deriyi nemlendirme ve yumuşatma etkisi bulunan ürünler arasında krem, merhem, losyon, banyo yağları ve sabun yerine geçen ürünler sayılabilmektedir.…”
Section: Gereç Ve Yöntemlerunclassified